Reactions in Electrodeposited Cu/Sn and Cu/Ni/Sn Nanoscale Multilayers for Interconnects - Chia, P.Y.; Haseeb, A.S. Md. Abdul; Mannan, S.H. (MDPI, 2016)
Miniaturization of electronic devices has led to the development of 3D IC packages which require ultra-small-scale interconnections. Such small interconnects can be completely converted into Cu-Sn based intermetallic compounds (IMCs) after reflow. In an effort to improve IMC based interconnects, an attempt is made to add Ni to Cu-Sn-based IMCs. Multilayer interconnects consisting of stacks of Cu/Sn/Cu/Sn/Cu or Cu/Ni/Sn/Ni/Sn/Cu/Ni/Sn/Ni/Cu with Ni = 35 nm, 70 nm, and 150 nm were electrodeposited sequentially using copper pyrophosphate, tin methanesulfonic, and nickel Watts baths, respectively. These multilayer interconnects were investigated under room temperature aging conditions and for solid-liquid reactions, where the samples were subjected to 250 °C reflow for 60 s and also 300 °C for 3600 s. The progress of the reaction in the multilayers was monitored by using X-ray Diffraction, Scanning Electron Microscope, and Energy dispersive X-ray Spectroscopy. FIB-milled samples were also prepared for investigation under room temperature aging conditions. Results show that by inserting a 70 nanometres thick Ni layer between copper and tin, premature reaction between Cu and Sn at room temperature can be avoided. During short reflow, the addition of Ni suppresses formation of Cu3Sn IMC. With increasing Ni thickness, Cu consumption is decreased and Ni starts acting as a barrier layer. On the other hand, during long reflow, two types of IMC were found in the Cu/Ni/Sn samples which are the (Cu,Ni)6Sn5 and (Cu,Ni)3Sn, respectively. Details of the reaction sequence and mechanisms are discussed.